A multicenter Phase II study of sorafenib in Japanese patients with advanced hepatocellular carcinoma and Child Pugh A and B class. (21st February 2018) - Suzuki, Eiichiro; Kaneko, Shuichi; Okusaka, Takuji; Ikeda, Masafumi; Yamaguchi, Kensei; Sugimoto, Rie; Aramaki, Takeshi; Asagi, Akinori; Yasui, Kohichiroh; Sano, Keiji; Hosokawa, Ayumu; Kato, Naoya; et al.
Abstract : To evaluate prospectively the efficacy and safety of sorafenib, which has been the first-line treatment for advanced hepatocellular carcinoma (HCC), in Japanese HCC patients (pts) with not only Child-Pugh (C-P) A class but also C-P B class. Abstract: Objective: To evaluate prospectively the efficacy and safety of sorafenib, which has been the first-line treatment for advanced hepatocellular carcinoma (HCC), in Japanese HCC patients (pts) with not only Child-Pugh (C-P) A class but also C-P B class. Methods: Sorafenib was administered orally at the dose of 400 mg twice daily for pts with HCC and liver function of C-P score of 5–8. Administration was continued until the detection of disease progression or appearance of unacceptable toxicity. The primary endpoint was time to progression (TTP), and toxicity and the secondary endpoints included objective response, overall survival (OS). Results: Forty C-P A pts and 12 C-P B pts were enrolled. The median TTP in the C-P A pts and C-P B pts was 3.3 months and 3.2 months, respectively. Among the pts with C-P A, complete response, partial response, and stable disease were achieved for 2.5%, 7.5% and 47.5%. Among the pts with C-P B, there were no treatment responses, 66.7% of pts had stable disease. The median OS in the C-P A pts and C-P B pts was 13.4 months and 7.4 months, respectively. With regard to toxicities, fewer C-P A pts experienced Grade 3/4 toxicities than C-P B pts (77.5% vs. 91.6%). There were no treatment-related deaths in either group of patients. Conclusions: This study shows sorafenib has similar effectiveness in the recent post-approval studies and is well-tolerated in Japanese pts with HCC and Child Pugh A class. Sorafenib should be used with great care for Child Pugh class B pts.